2017
DOI: 10.1007/s00784-017-2104-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of periodontitis history on implant success: a long-term evaluation during supportive periodontal therapy in a university setting

Abstract: The presence of a good periodontal maintenance program with preceding successful active periodontal treatment seems to be indispensable components of successful implant treatment in patients with history of chronic periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 61 publications
5
27
0
Order By: Relevance
“…Some previous studies have proved the capacity of a regular SPT in overlap susceptibility of periodontitis subjects, resulting in high success rates (Sgolastra et al., ; Sousa et al., ; Zangrando et al., ). Recently, two studies showed similar long‐term results (success and survival), after a SPT/PIMT, in susceptible (previously periodontitis subjects) and nonsusceptible patients (history of periodontal healthy) to those related in the present manuscript (Graetz et al., ; Tan, Ong, & Lang, ). Meanwhile, as also demonstrated in both studies, there was a trend in peri‐implant bleeding.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Some previous studies have proved the capacity of a regular SPT in overlap susceptibility of periodontitis subjects, resulting in high success rates (Sgolastra et al., ; Sousa et al., ; Zangrando et al., ). Recently, two studies showed similar long‐term results (success and survival), after a SPT/PIMT, in susceptible (previously periodontitis subjects) and nonsusceptible patients (history of periodontal healthy) to those related in the present manuscript (Graetz et al., ; Tan, Ong, & Lang, ). Meanwhile, as also demonstrated in both studies, there was a trend in peri‐implant bleeding.…”
Section: Discussionsupporting
confidence: 80%
“…(), also presenting higher BoP scores, patients with history of periodontitis performed similarly to healthy ones after 6‐year follow‐up due to a rigid regular SPT programme. Indeed, predictive factors for peri‐implant diseases cited by recent and similar studies were residual pockets (Graetz et al., ; Zangrando et al., ), non‐attendance to the periodontal maintenance programme, smoking (Zangrando et al., ), bone height and age (Graetz et al., ). These aspects, altogether, reaffirm a well‐known role of supportive therapy, what should be reinforced in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Although, recent evidence has indicated that history of periodontitis is identified as a predisposing factor for implant loss, 42 peri-implantitis 43 and higher PD and BL around the implants, 44 scarce information is available about its effect on the outcome of RST of peri-implantitis in literature. Although, recent evidence has indicated that history of periodontitis is identified as a predisposing factor for implant loss, 42 peri-implantitis 43 and higher PD and BL around the implants, 44 scarce information is available about its effect on the outcome of RST of peri-implantitis in literature.…”
Section: Discussionmentioning
confidence: 99%
“…According to the model, "history of periodontitis" negatively affected our primary outcome. Although, recent evidence has indicated that history of periodontitis is identified as a predisposing factor for implant loss, 42 peri-implantitis 43 and higher PD and BL around the implants, 44 scarce information is available about its effect on the outcome of RST of peri-implantitis in literature. "Implant location" was found as an another prognostic factor in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Although dental-implant rehabilitation has been reported as safe and successful in the general population, 4 some factors can interfere in the predictability of the dental implant outcomes, 5 including history of periodontitis. 6,7 History of periodontitis, especially aggressive periodontitis, is a risk factor for the long-term survival of dental implants. 6,8 Monje et al 9 showed that the risk ratio for dental implant failure in patients with a history of GAP was significantly higher than in healthy patients (4.0) and in those with chronic periodontitis (3.97), which is consistent with recently published data.…”
Section: Introductionmentioning
confidence: 99%